[Zsuzsa Perjési 1]
walk in the Tatra-mountain, little bridge, tourist-lodge, waterfall, lake among the mountains, snow-storm in winter, Schnittenhohen, Konig-see, Innsbruck, tram, funicular, Badgastein, Klagenfurt, (in the end Pathe-Baby with rooster symbol)